Gerakan Pencegahan Stunting melalui Peningkatan Pengetahuan Ibu dengan Metode Emotional Demonstration di Wilayah Kerja Puskesmas Mungo - Vivi Triana; Meilita Wise Utami; Putri Adiratna; Nessa Iskandar; Adinda Ismira; Tantri Febria; Vina Febriani; Andini Agesta Putri; Nadhiyatul Alhamda; Anggun Febrina (Jurnal Abdimas Kesehatan (JAK), 2023)
Based on the analysis of the working area of the Mungo Health Center, namely Luak District, and 50 Kota District, it was found that there was a trend of increasing stunting cases every year. For this reason, stunting is a priority public health problem that must be resolved immediately. The cause of stunting is closely related to the lack of knowledge of mothers about parenting and balanced nutrition in children. One of the most effective efforts to increase mothers' knowledge is to provide education through the Emo-Demo counseling method (Emotional demonstration). Emo-Demo is a very participatory activity guide that aims to convey simple messages in a fun way. It is hoped that this activity will help increase mothers' knowledge, in an effort to prevent and reduce the prevalence of stunting in the working area of the Mungo Health Center. The target of counseling activities is mothers of toddlers with indications of stunting. Based on the results of the analysis (pre-test and post-test) there was an increase in mothers' knowledge and awareness regarding parenting and stunting prevention as indicated by an increase in the average knowledge before and after counseling. Thus this Emo-Demo activity is proven to be an innovative approach to educational communication because it can increase changes in mothers' knowledge related to parenting and balanced nutrition to toddlers.